Free radical scavenging and COX-2 inhibition by simple colon metabolites of polyphenols: A theoretical approach. (December 2016) - Amić, Ana; Marković, Zoran; Marković, Jasmina M. Dimitrić; Jeremić, Svetlana; Lučić, Bono; Amić, Dragan
Graphical abstract: Highlights: 3-Hydroxyphenylacetic and 4-hydroxyphenylpropionic acid were theoretically studied. These colon metabolites of polyphenols exert high free radical scavenging potency. Docking analysis indicated dianions of these acids as potent inhibitors of COX-2. As abundant metabolites, these acids could be effective in situ anticancer agents. Abstract: Free radical scavenging and inhibitory potency against cyclooxygenase-2 (COX-2) by two abundant colon metabolites of polyphenols, i.e., 3-hydroxyphenylacetic acid (3-HPAA) and 4-hydroxyphenylpropionic acid (4-HPPA) were theoretically studied. Different free radical scavenging mechanisms are investigated in water and pentyl ethanoate as a solvent. By considering electronic properties of scavenged free radicals, hydrogen atom transfer (HAT) and sequential proton loss electron transfer (SPLET) mechanisms are found to be thermodynamically probable and competitive processes in both media. The Gibbs free energy change for reaction of inactivation of free radicals indicates 3-HPAA and 4-HPPA as potent scavengers. Their reactivity toward free radicals was predicted to decrease as follows: hydroxyl >> alkoxyls > phenoxyl ≈ peroxyls >> superoxide. Shown free radical scavenging potency of 3-HPAA and 4-HPPA along with their high μM concentration produced by microbial colon degradation of polyphenols could enable at least in situ inactivation of free radicals. Docking analysis with structural forms of 3-HPAA and 4-HPPA indicates dianionic ligands as potent inhibitors of COX-2, an inducible enzyme involved in colon carcinogenesis. Obtained results suggest that suppressing levels of free radicals and COX-2 could be achieved by 3-HPAA and 4-HPPA indicating that these compounds may contribute to reduced risk of colon cancer development.